11-4k=-3k+5

Simple and best practice solution for 11-4k=-3k+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11-4k=-3k+5 equation:


11-4k=-3k+5

We simplify the equation to the form, which is simple to understand
11-4k=-3k+5

We move all terms containing k to the left and all other terms to the right.
-4k+3k=+5-11

We simplify left and right side of the equation.
-1k=-6

We divide both sides of the equation by -1 to get k.
k=6

See similar equations:

| 4x-8=72 | | 16-n=9n-4 | | 16*30=x+6(2x-4) | | 16x^2=40x-18 | | 4x-1=-13 | | v+10-1=-15-2v | | 3x-27=-39 | | 2x^2+15x+7=7 | | -2x+10=-11-9x | | 5n+3n+-n+5=26 | | 5+8(x-2)= | | 12-6b-2b=9-9b | | 26=7x+5 | | 16x^3-54=0 | | 1+7n=-6+8n | | 7x+12=-4x+1+9x-5 | | -17+9x=x+7 | | 3t^2+3t-1=0 | | (2x+5)(x-7)= | | u^2+18u=-71 | | 7r-1=3+3r | | 2X=3X+4 | | 64x^3+125=0 | | 2m+8-2=-3-7m | | 4400=-10x^2+256x+3500 | | x+4x-5= | | 19+2n=5n-2 | | 2(2z-4)=3(z-4) | | c^2+10c=-3 | | x-7x^2=0 | | -12+5x=-5x+8x | | 6(-4-x)=30 |

Equations solver categories